Peranan Wahyu Ilahi dalam Kanonisasi Alkitab - Telaumbanua, Yohanes; Suhadi, Suhadi (Jurnal Teologi Berita Hidup, 2023)
The content of the Bible is that God Himself breathed out or inspired the Bible, so the Bible is true. Along with history attacks against the inerrancy of the Bible have occurred. Errantists and Inerrantists emerged, both of whom had thinkers who could deal with the facts of several parts of the Bible in question and both parties read the conclusions of their opponents. Then it is very important to remember that the Bible validates itself because the books were breathed into God's breath (2 Timothy 3:16). In other words, canonicality is inherent in these books, because they come from God. Likewise, interpreting the Bible by the light of the Holy Spirit enables us to believe in the truth of the Bible. So, the researcher used qualitative research methods with a descriptive literature approach. The descriptive literature approach is a data collection technique based on library research as supporting material for theory formulation.Isi alkitab ialah Allah sendiri yang meniupkan keluar atau mengilhami Alkitab, maka Alkitab adalah benar. Seiring dengan sejarah serangan-serangan terhadap ketidakkeliruan Alkitab pun terjadi. Muncul kaum errantis dan kaum inerrantis, keduanya mempunyai pemikir-pemikir yang cakap menghadapi fakta-fakta beberapa bagian-bagian Alkitab yang dipermasalahkan dan kedua pihak membaca kesimpulan-kesimpulan dari lawannya. Kemudian amat penting diingat bahwa Alkitab mengesahkan dirinya sendiri karena kitab-kitab ditiupkan oleh napas Allah (2Tim. 3:16). Dengan kata lain, kekanonannya telah melekat di dalam kitab-kitab itu, karena berasal dari Allah. Demikian pula penafsiran Alkitab oleh terang Roh Kudus memampukan kita mempercayai kebenaran Alkitab. maka peneliti menggunakan metode penelitian kualitatif dengan pendekatan deskriptif literatur. pendekatan deskriptif literatur ialah teknik pengumpulan data berdasarkan kajian pustaka sebagai bahan pendukung perumusan teori.